Survival outcomes of allogeneic hematopoietic cell transplants with EBV‐positive or EBV‐negative post‐transplant lymphoproliferative disorder, A CIBMTR study. Issue 5 (31st July 2019) - Naik, Seema; Riches, Marcie; Hari, Parameswaran; Kim, Soyoung; Chen, Min; Bachier, Carlos; Shaughnessy, Paul; Hill, Joshua; Ljungman, Per; Battiwalla, Minoo; Chhabra, Saurabh; Daly, Andrew; et al.
Abstract: Background: Post‐transplant lymphoproliferative disorders (PTLD) are associated with significant morbidity and mortality following allogeneic hematopoietic cell transplant (alloHCT). Although most PTLD is EBV‐positive (EBV pos ), EBV‐negative (EBV neg ) PTLD is reported, yet its incidence and clinical impact remain largely undefined. Furthermore, factors at the time of transplant impacting survival following PTLD are not well described. Methods: Between 2002 and 2014, 432 cases of PTLD following alloHCT were reported to the Center for International Blood and Marrow Transplant Research (CIBMTR). After exclusions, 267 cases (EBV pos  = 222, 83%; EBV neg  = 45, 17%) were analyzed. Results: Two hundred and eight patients (78%) received in vivo T‐cell depletion (TCD) with either anti‐thymocyte globulin (ATG) or alemtuzumab. Incidence of PTLD was highest using umbilical cord donors (UCB, 1.60%) and lowest using matched related donors (MRD, 0.40%). Clinical features and histology did not significantly differ among EBV pos or EBV neg PTLD cases except that absolute lymphocyte count recovery was slower, and CMV reactivation was later in EBV neg PTLD [EBV pos 32 (5‐95) days versus EBV neg 47 (10‐70) days, P  = .016]. There was no impact on survival by EBV status in multivariable analysis [EBV neg RR 1.42, 95% CI 0.94‐2.15, P  = .097]. Conclusions: There is no difference in survival outcomes for patients with EBV pos or EBV neg PTLD occurring following alloHCT and 1‐year survival is poor. Features of conditioning and use of serotherapy remain important.